Wild Relics in an Urban Landscape: A Look at Raccoon Representations in Newspaper Media - Luther, Erin (UnderCurrents: Journal of Critical Environmental Studies, 2007)
As global urbanization gains momentum, human experience is increasingly restricted to dense urban environments; a new urban human looks out through the window, rejecting and inviting the "wild" in complex ways. This paper analyzes a sampling of newspaper articles that probe the dimensions of the urban wild by following the media intersection between humans and a commonly encountered wild animal, the raccoon. This intersection is typical of many urban human-wildlife interactions in the sense that it is characterized by a fierce ambivalence (Griffiths, Poulter, & Sibley, 2000). The human-raccoon relationship, however, captures this ambivalence in a way not seen with other urban wildlife. Conflicted feelings about raccoons challenge the psychic boundaries of both human and animal domesticity in an urban context.